2009
DOI: 10.1111/j.1741-3737.2009.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents With Nonresident Fathers: Are Daughters More Disadvantaged Than Sons?

Abstract: This study examined sons' and daughters' involvement with nonresident fathers and associated outcomes (N=4,663). Results indicate that sons and daughters report equal involvement with nonresident fathers on most measures of father investment, although sons report more overnight visits, sports, and movies, and feeling closer to their fathers compared to daughters. Sons and daughters generally benefit from nonresident father involvement in the same way in internalizing and externalizing problems and grades. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 41 publications
(52 reference statements)
0
32
0
1
Order By: Relevance
“…Other findings suggest that paternal influence decreases antisocial behavior (Kosterman, Haggerty, Spoth, & Redmond, 2004) and sexual risk taking (Peterson, 2007;Stein, Milburn, Zane, & Rotheram-Borus, 2009) in daughters. Closeness and affirmation of fathers reduced internalization of problems in girls (Mitchell, Booth, & King, 2009), as well as enhanced women's comfort with their sexuality as adults (Scheffler & Naus, 1999). However, the literature is limited in exploration of the interior aspects of father-daughter relationships.…”
Section: Scholarship On Fathers and Daughtersmentioning
confidence: 97%
“…Other findings suggest that paternal influence decreases antisocial behavior (Kosterman, Haggerty, Spoth, & Redmond, 2004) and sexual risk taking (Peterson, 2007;Stein, Milburn, Zane, & Rotheram-Borus, 2009) in daughters. Closeness and affirmation of fathers reduced internalization of problems in girls (Mitchell, Booth, & King, 2009), as well as enhanced women's comfort with their sexuality as adults (Scheffler & Naus, 1999). However, the literature is limited in exploration of the interior aspects of father-daughter relationships.…”
Section: Scholarship On Fathers and Daughtersmentioning
confidence: 97%
“…Recent literature has brought to light that father involvement continues to be important even after children reach adolescence (Mitchell, Booth, & King, 2009). Paternal involvement in adolescence is associated with higher levels of well-being in adolescents (Cookston & Finlay, 2006;Mitchell et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Paternal involvement in adolescence is associated with higher levels of well-being in adolescents (Cookston & Finlay, 2006;Mitchell et al, 2009). Flouri and Buchanan (2003) found the relationship between paternal involvement and adolescent well-being statistically significant, and the findings of other studies found that reported father involvement is associated with less behavioural problems during adolescence (Amato & Rivera, 1999;Harris et al, 1998;Mitchell et al, 2009). Interestingly, Flouri and Buchanan (2003) found that paternal involvement had a stronger effect than maternal involvement on adolescent happiness and was equally predictive for sons' and daughters' reported levels of happiness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations